RF and baseband techniques for software defined radio - Kenington, Peter B. (Boston : Artech House, 2005)
This authoritative book gives you new perspective on the RF and analog hardware and systems design aspects of software defined radio. It delves into the architecture of transmitters and receivers that make software-defined radio a reality. Covering both the practical aspects and underpinnings of these architectures, the book details all key RF and analog baseband components and sub-systems, from the converters that interface with DSPs and ASICs through to the duplexer feeding the antenna. It enables you to select the right technique for any application by providing alternatives for implementing the main system components.
Introduction$1 (BWhat is Software Defined Radio. The Requirements for Software-Defined Radio. The Benefits of Multi-Standard Terminals. Operational Requirements. Business Models for Software-Defined Radio. New Base Station and Network Architectures. Smart Antenna Systems. Projects and Sources of Information for Software-Defined Radio. Organization of the Text. References. Basic Architecture of a Software-Defined Radio$1 (BIdeal Software-Defined Radio Architecture. Required Hardware Specifications. Digital Aspects of a Software Radio. Current Technology Limitations. Impact of Superconducting Technologies on Software Defined Radio. References. Flexible RF Receiver Architectures$1 (BIntroduction. Receiver Architecture Options. Implementation of a Digital Receiver. Multi-Band and General Coverage Systems. The Problem of the Duplexer. Achieving Image Reduction. Dynamic Range Enhancement. Influence of Phase-Noise on EVM for a Linear Transceiver. Relationship between EVM, PCDE, and Rho. References. Flexible Transmitters and PAS$1 (BIntroduction. Differences in PA Requirements and for Base-Stations and Handsets. Basic Upconversion Architectures. Broadband Quadrate Techniques. Linearization Applied to Software Radio Transmitters. Power Amplifier Linearization Techniques. Transmitter Linearization Techniques. RF Synthesis Techniques. Power Efficiency. References.s
Includes bibliographical references and index.
1
Keywords: Software radio